Ramaphosa’s turn: Can Cyril save South Africa? (Tafelberg, 2018. ISBN:0624085554) Ralph Mathekga (Yesterday & Today Journal for History Education in South Africa and abroad, 2021)
The book themed and titled Ramaphosa’s turn: Can Cyril save South Africa? Is a necessary book as the “new dawn” has dawned upon us and many South Africans are desperate for a corruption free and economically healthy country after the Zuma era. The introduction intrigues the reader with critical questions such as “why should a billionaire businessman want to be president of a volatile society with such deep inequalities as ours?” herein, is the genesis of understanding how Ramaphosa “won the presidency, but lost the power play” (p. 16.), and how he will manoeuvre his saving of the country as many desperately need him to. The introduction further lays down the thorns that could make his reign difficult, example, an ideologically divided African National Congress (ANC).
Keywords: Ramaphosa’s turn; Ralph Mathekga; corruption